Search for flavour-changing neutral current top-quark decays to qZ in pp collision data collected with the ATLAS detector at √s = 8 TeV - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Davygora, Yuriy; Djuvsland, Julia Isabell; Dunford, Monica; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (The European physical journal. C, Particles and fields, 2016)
A search for the flavour-changing neutral-current decay t→qZ is presented. Data collected by the ATLAS detector during 2012 from proton–proton collisions at the Large Hadron Collider at a centre-of-mass energy of s√=8 TeV, corresponding to an integrated luminosity of 20.3 fb−1, are analysed. Top-quark pair-production events with one top quark decaying through the t→qZ (q=u,c) channel and the other through the dominant Standard Model mode t→bW are considered as signal. Only the decays of the Z boson to charged leptons and leptonic W boson decays are used. No evidence for a signal is found and an observed (expected) upper limit on the t→qZ branching ratio of 7×10−4 (8×10−4) is set at the 95 % confidence level.
*ATLAS Collaboration: G. Aad, C.F. Anders, V. Andrei, A.E. Baas, O. Brandt, Y. Davygora, J.I. Djuvsland, M. Dunford, M.P. Geisler, M. Giulini, P. Hanke. J. Jongmanns, E.-E. Kluge, M. Kretz, A. Kugel, V.S. Lang, M. Lisovyi, K. Meier, H. Meyer zu Theenhausen, D.I. Narrias Villar, M. Sahinsoy, S. Schaetzel, V. Scharf, S. Schmitt, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, R. Stamen, P. Starovoitov, M. Wessels [und sehr viele weitere Personen]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 17.06.2020